Риторичні питання в контексті ідіостилю Лонга (на матеріалі роману „Дафніс і Хлоя”) - Chakal (Makar), Inesa (Видавництво ХНУ імені В.Н.Каразіна, 2014)
У статті охарактеризовано риторичні питання у тексті роману давньогрецького письменника кінця ІІ ст. н.е. Лонга „Дафніс і Хлоя”. Доведено, що залежно від лексичного наповнення риторичні питання посилюють різноманітні емоційно-оцінні значеннєві відтінки: здивування, радості, суму, сумніву, страждання тощо. З'ясовано синтаксично-стилістичну природу риторичних питань, визначено їхню роль для ідіостилю письменника. In the article rhetorical questions are described in the text of the novel of ancient greek writer of the end of the 2nd century Longus „Daphnis and Chloe”. It is well-proven that depending on the lexical filling rhetorical questions strengthen various emotionaly-estimative inflections: surprise, gladness, sadness, doubt, suffering etc. Syntactic and stylistic nature of rhetorical questions is found out, their role for writer’s idiostyle is discovered.
The rhetorical questions in the context of Longus’ idiostyle (based on the text of the novel „Daphnis and Chloe”)
Keywords: риторичне питання; риторична фігура; інтонація; ідіостиль; Лонг; rhetorical question; rhetorical figure; intonation; idiostyle; Longus